2012
DOI: 10.1002/iub.1035
|View full text |Cite
|
Sign up to set email alerts
|

NSAIDs induce apoptosis in nonproliferating ovarian cancer cells and inhibit tumor growth in vivo

Abstract: Ovarian cancer (OC) is one of the most lethal gynaecological cancers, which usually has a poor prognosis due to late diagnosis. A large percentage of the OC cell population is in a nonproliferating and quiescent stage, which poses a barrier to success when using most chemotherapeutic agents. Recent studies have shown that several nonsteroidal anti‐inflammatory drugs (NSAIDs) are effective in the treatment of OC. Furthermore, we have previously described the molecular mechanisms of NSAIDs' induction of cancer a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 38 publications
1
24
0
Order By: Relevance
“…Similarly, it was claimed that flurbiprofen was one of the powerful NSAID inducer of apoptosis in ovarian cancer cells. Also, combination of sulindac sulfide targeting proliferative cells and flurbiprofen targeting nonproliferative cells weakened tumor growth more powerfully and effectively as compared with these substances in single form (Duncan et al, 2012). Similar to many of the mentioned findings, it has been reported that r-flurbiprofen inhibited colon adenomas in mice, reduced proliferation in pituitary adenoma cells in vitro and induced apoptosis (Liu et al, 2012).…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Similarly, it was claimed that flurbiprofen was one of the powerful NSAID inducer of apoptosis in ovarian cancer cells. Also, combination of sulindac sulfide targeting proliferative cells and flurbiprofen targeting nonproliferative cells weakened tumor growth more powerfully and effectively as compared with these substances in single form (Duncan et al, 2012). Similar to many of the mentioned findings, it has been reported that r-flurbiprofen inhibited colon adenomas in mice, reduced proliferation in pituitary adenoma cells in vitro and induced apoptosis (Liu et al, 2012).…”
Section: Discussionmentioning
confidence: 67%
“…Again, a study showed that flurbiprofen induced LDH release associated with cytotoxicity in monolayer rat hepatocytes culture (Jurima-Romet et al, 1994;Masubuchi et al, 1998). Flurbiprofen induced apoptosis in human polymorphonuclear neutrophils (Zielinska-Przyjemska et al, 2008), did not protect from oxidative stress induced by aluminum in rats (Nivsarkar et al, 2008) and reduced the growth of ovarian tumors (Duncan et al, 2012). After a comprehensive investigation, it was indicated that mutagenicity studies of flurbiprofen are not sufficient.…”
Section: Introductionmentioning
confidence: 97%
“…[10,11] In recent years, there has been an increased interest in the antitumour activity of NSAIDs due to at least three reasons: (1) COX-2 is found to be overexpressed in many cancers thus making it an attractive therapeutic target for the prevention and treatment of a number of malignancies [11,12]; (2) chronic inflammation has been proved to play an important role in cancer development and progression [13,14]; (3) NSAIDs are used also by oncology patients and the 'relationships' between these drugs and cancer cells have to be better clarified. [15] Numerous studies have suggested that aspirin and/or other NSAIDs can be effective in the prevention and/or treatment of malignancies, such as cancers of the colon, [16] breast, [17,18] lung, [19] pancreas, [20] prostate, [21,22] ovarium, [23] squamous cell carcinoma and melanoma, [24] etc. Different NSAIDs have been reported to inhibit the growth and survival of cell lines established from a wide variety of cancers, including gastric cancer, [25,26] cancers of the colon, [27] lung, [28] urinary bladder, [29] osteosarcoma, [30] etc.…”
Section: Introductionmentioning
confidence: 99%
“…Other non-opiate therapies that have been shown to reduce CIBP and disease progression in preclinical models of bone cancer are NSAIDS and inhibitors of COX-2 3,11,21,22,45,48 . Both these therapies have also been shown to slow the growth of a wide variety of cancers and are commonly used as a first line therapy to treat CIBP 3,11,21,22,45,48 .…”
Section: Discussionmentioning
confidence: 99%